2008
DOI: 10.1086/528786
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of the Parker Scenario for Coronal Heating

Abstract: The Parker or field line tangling model of coronal heating is studied comprehensively via long-time high-resolution simulations of the dynamics of a coronal loop in cartesian geometry within the framework of reduced magnetohydrodynamics (RMHD). Slow photospheric motions induce a Poynting flux which saturates by driving an anisotropic turbulent cascade dominated by magnetic energy. In physical space this corresponds to a magnetic topology where magnetic field lines are barely entangled, nevertheless current she… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
339
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(372 citation statements)
references
References 48 publications
(67 reference statements)
25
339
3
4
Order By: Relevance
“…1 of [90]). In that original work, the magnetic field is (roughly) constant in space, which is similar to three-dimensional experiments without gravity [15]. Therefore, also the currents and thus the Ohmic heating will be (roughly) constant in space.…”
Section: (E) Nanoflares Nanoflare Storms and Braiding Of Fieldlinesmentioning
confidence: 60%
See 1 more Smart Citation
“…1 of [90]). In that original work, the magnetic field is (roughly) constant in space, which is similar to three-dimensional experiments without gravity [15]. Therefore, also the currents and thus the Ohmic heating will be (roughly) constant in space.…”
Section: (E) Nanoflares Nanoflare Storms and Braiding Of Fieldlinesmentioning
confidence: 60%
“…In particular, these models will also describe the variability of the heating in the direction perpendicular to the fieldlines. Solving a simplified problem, it has been shown that current sheets are roughly aligned with the magnetic field and result in a heat input intermittent in space and time [13,15]. These current sheets are also seen in three-dimensional models in a more realistic atmospheric set-up (albeit at a reduced resolution) as narrow fingers of enhanced heat input; see figs.…”
Section: (B) Heat Input With Height and Along Individual Fieldlinesmentioning
confidence: 95%
“…Such braiding is a measure of how often different field lines cross each other in space Berger and Asgari-Targhi 2009 and is supported by MHD models (Gudiksen and Nordlund 2005;Rappazzo et al 2008;van Ballegooijen et al 2011). These braided small-scale field structures efficiently heat the coronal environment by the dissipation of electric currents, where oppositely directed magnetic fields are found in close vicinity to each other (Parker 1983, see also Cirtain et al 2013;Thalmann et al 2014).…”
Section: Energy Buildup and Storagementioning
confidence: 94%
“…The first family of these models involve transient and alternative currents (AC), either created by MHD turbulence (e.g. Buchlin et al 2003;Gudiksen & Nordlund 2005;Rappazzo et al 2008) or by the resistive damping of nonlinear magnetoacoustic waves (e.g. Heyvaerts & Priest 1983;Einaudi & Mok 1987;Parker 1991;Ofman & Davila 1995).…”
Section: Introductionmentioning
confidence: 99%